HISTORICAL AND ANALYTICAL REVIEW OF SOCIAL NETWORKING TECHNOLOGIES AND PROSPECTS OF THEIR USE IN TRAINING - Olga P. Pinchuk (Information technologies and learning tools, 2015)
The article presents a brief historical description of the origin and the study of social networks, the results of current research in the philosophical and psychological sciences, social communication and economics. The current state of educational research of electronic social networking and forming of practical experience of their use are analyzed. The results of studies of social networks are analyzed in terms of their formation in relation with increasing globalized communication space and the transformation of the old society and the emergence of new practices of interaction between social subjects in various fields of society, including education. In the use of electronic social networking author sees potential for solving problems of synchronizing of different educational formats for building a coherent individual educational trajectory.